2013
DOI: 10.1039/c3ta12077e
|View full text |Cite
|
Sign up to set email alerts
|

TiC/Pt composite catalyst as counter electrode for dye-sensitized solar cells with long-term stability and high efficiency

Abstract: Title : TiC/Pt composite catalyst as counter electrode for long-term stable and high effi ciency dye-sensitized solar cellsLow-cost and high-effi ciency TiC/Pt composite is successfully introduced into large scale dye-sensitized solar cells (DSCs) as a counter electrode catalyst. The TiC/Pt-based DSC shows ideal results as compared to the Pt-based DSC. This research is important for reducing the cost of DSCs and for the industrialization of DSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Wu et al fabricated composite TiC-Pt electrodes via a chemical method and used them as DSSC counter electrodes (CEs). [9] In their work, a high efficiency (7.63%, based on I − /I 3 electrolyte) was achieved from a TiC-Pt CE. This was higher than those of pure TiC (6.40%) and Pt (7.16%) CEs.…”
Section: Introductionmentioning
confidence: 98%
“…Wu et al fabricated composite TiC-Pt electrodes via a chemical method and used them as DSSC counter electrodes (CEs). [9] In their work, a high efficiency (7.63%, based on I − /I 3 electrolyte) was achieved from a TiC-Pt CE. This was higher than those of pure TiC (6.40%) and Pt (7.16%) CEs.…”
Section: Introductionmentioning
confidence: 98%
“…Unlike the semiconductor, dye, and redox shuttle components, counter electrode (CE) catalysts are often overlooked. Fortunately, CE catalysts begun to attract increasing attention, as a class of new CE catalysts, such as carbon materials, [9][10][11][12] organic polymers, [13][14][15][16] and metal compounds [17][18][19][20][21][22][23][24][25][26][27][28][29][30] have been applied to replace conventional noble Pt CE. Among these Pt-free materials, carbon is a promising CE catalyst for use in DSCs because of its low cost, high conductivity, high catalytic activity, ready availability, high thermal stability, and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, due to its limited availability and costliness, finding alternatives for Pt in the DSCs system is crucial. 5 In recent studies, some inorganic materials have shown excellent electrocatalytic activity in reducing triiodide, which will possess important candidacy as promising alternative CE materials in DSCs.…”
Section: Introductionmentioning
confidence: 99%